Heterogeneity of Cerebral Blood Flow in Alzheimer Disease and Vascular Dementia - Yoshikawa, Takuya; Murase, Kenya; Oku, Naohiko; Imaizumi, Masao; Takasawa, Masashi; Rishu, Piao; Kimura, Yasuyuki; Ikejiri, Yoshitaka; Kitagawa, Kazuo; Hori, Masatsugu; Hatazawa, Jun (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Alzheimer disease (AD) and vascular dementia (VaD) are the two major diseases that cause dementia, and early diagnosis is important. Single photon emission CT (SPECT) of cerebral blood flow (CBF) is used for the early detection of dementia and as an auxiliary method for follow-up. AD shows reduced posterior blood flow and VaD manifests reduced anterior blood flow on CBF SPECT images. We examined the usefulness of 3D fractal analysis of CBF SPECT images to objectively quantify the heterogeneity of CBF in patients with AD and VaD.METHODS: Thirty-two patients with AD and 22 with VaD based on neuropsychologic tests and imaging findings, as well as 20 age-matched control subjects underwent technetium-99m hexamethyl propyleneamine oxime CBF SPECT. We then conducted statistical image processing by 3D fractal analysis on reconstructed data. Fractal dimension, an index of heterogeneity, was then calculated for the whole brain, as well as for the anterior and posterior regions of the brain. A higher fractal dimension indicates that the CBF SPECT image is uneven. The ratio of fractal dimension of the anterior region to fractal dimension of the posterior region (A/P ratio) was calculated. Heterogeneity of CBF was compared among the AD, VaD, and control groups.RESULTS: Fractal dimensions of the AD, VaD, and control groups were 1.072 ± 0.179 (mean ± SD), 1.005 ± 0.156, and 0.806 ± 0.06, respectively. A significant difference of fractal dimension was noted between the control group and the two types of dementia (P < .0001); however, no significant difference was noted between the AD and VaD groups. The A/P ratios of the AD and VaD groups were significantly different (0.952 and 1.163, respectively; P < .01).CONCLUSION: Analysis of CBF SPECT images quantitatively showed that the fractal dimension was significantly higher (indicating heterogeneity) in patients with AD and VaD when compared with age-matched control subjects. Comparison of the A/P ratio on CBF SPECT images between AD and VaD groups showed that the heterogeneity of CBF was posterior-dominant for AD and anterior-dominant for VaD. Thus, 3D fractal analysis enabled a simple and objective evaluation of the heterogeneity of CBF in patients with AD and VaD.